Filosofia, filologia, e il «senso delle masse» - Dainotto, Roberto (International Gramsci Journal, 2023)
Through a close reading of Q1§47, “Hegel and Associationism”, the essay delves into a dominant problematic of the Prison Notebooks: how to organize a revolutionary mass movements when the modern “integral State” establishes its hegemony by organizing public opinion and disorganizing dissent? The question entails, from a Gramscian perspective, the possibility of resolving and organically synthesizing a series of antinomies that State hegemony tends to keep separated, both conceptually and practically: coercion and consent; intellectuals and masses; theory and practice.